Autonomous learning and creative cognition: the mediating effect of gifted students’ self-efficacy - Orakcı, Şenol (Frontiers in Psychology, 2025)
Dear Editor and Reviewers: Thank you for your valuable comments and efforts on our manuscript. We have carefully reviewed your feedback and made corresponding revisions, which are marked in red. Please see our detailed responses below.All the amendments and additions were shown in RED both in revision parts below and the revised manuscript.well as the rationale leading to the proposed hypotheses. It is recommended to increase empirical evidence on these topics with research published in the last five years.Thank you for the opportunity to improve the text. We have carefully studied the comments and suggestions and revised our paper accordingly. The following are our point-by-point responses to the general and specific comments. We hope that the revisions are acceptable and that our responses adequately address the comments.We have included empirical evidence in the last five years:….Additionally, Hermita et al. ( 2023) found that an autonomous learning application in STEM classes improved students' critical thinking abilities in their quasi-experimental research. To put it another way, encouraging critical and creative thinking can help them become more autonomous since autonomous learning requires critical and creative thinking and behavior as well as correct judgment based on interactions, experiences, and observations when analyzing, organizing, and evaluating information…. ….A study by Demir and Cetinbaş (2023) revealed that critical thinking was a strong predictor of autonomous learning in the regression analysis. Highly capable students' autonomous learning is impacted by any shift in critical thinking (Demir & Cetinbas, 2023). Another study by Arslan et al. (2023) also showed that autonomous learning significantly predicted both problem-solving and creative cognition…. …Self-Directed Learning (SDL) states that people are inherently driven to learn new things and take on challenges, and that they have a natural tendency to acquire autonomous regulation of behavior (Ten Cate et al., 2011). Common definitions of SDL include students' capacity and disposition to create, pursue, and assess their own learning goals as well as their ability to assess their own learning process and outcomes (Abd-El-Fattah, 2010; van Woezik et al.,